Faculty acceptance and use of generative artificial intelligence in their practice - Nevárez Montes, Julián; Elizondo-Garcia, Josemaria (Frontiers in Education, 2025)
The effective integration of Generative Artificial Intelligence (GenAI) into educational practices holds promise for enhancing teaching and learning processes. Examining faculty acceptance and use of GenAI implementation can provide valuable insights into the conditions necessary for its successful application. This study consisted of a survey to measure the acceptance and use of GenAI in the educational practice of 208 faculty members at a private university in Mexico. The survey instrument used integrates elements of the Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA). The original questionnaire was translated into Spanish and validated by experts to ensure reliability and validity in the new context. Overall, acceptance dimensions obtained middle-high results. Behavioral intention obtained the highest values whereas Subjective norm obtained the lowest values. Significant differences in GenAI acceptance regarding faculty disciplines and sociodemographics were not identified. Also, faculty GenAI acceptance is positively moderate correlated with faculty GenAI use to produce text. The identified acceptance level among faculty toward the use of GenAI in educational environments leads to expect a promising future for its integration into teaching and learning practices. In addition, further research on GenAI integration for student use and the impact of faculty training on the effective use of GenAI in educational settings are encouraged.